Analisis Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa Akuntansi Terhadap Profesi Akuntan Publik - Warna Dwi Safitri; Ceacilia Srimindarti (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
This study aims to analyze and examine the influence of the factors that influence the interest of accounting students in the public accounting profession. The sample taken in this study used the convenience sampling method. The sample in this study amounted to 100 respondents from accounting students for the 2018-2020 class. The results of this study explain that financial rewards and labor market considerations have a significant positive effect on student interest as a public accounting profession, while gender does not affect student interest as a public accounting profession. Keywords : Student Interests, Gender, Financial Rewards, Job Market Considerations